Pemanfaatan Program Hospital Corporate Social Responsible (CSR) dalam meningkatkan Pemasaran Rumah Sakit Umum Hidayah Boyolali - Hesty Latifa Noor; Rahaju Muljo Wulandari; Lailathul Fitria Nandra (Lembaga Pengembangan Kinerja Dosen, 2025)
Hidayah Boyolali General Hospital (RSU) was established by the Yayasan Dua September Boyolali and began operating since September 2, 2011 as a medical center, then officially became a hospital in May 2012 through the Decree of the Head of the Investment and Integrated Licensing Service Agency of Boyolali Regency No. 503/002/30 of 2012. As a type D private hospital, RSU Hidayah Boyolali is committed to providing professional health services that are oriented towards customer satisfaction. In the face of fierce competition between hospitals, especially in the Boyolali area, RSU Hidayah seeks to develop an effective marketing strategy to increase the number of patient visits. This Community Service activity aims to improve the knowledge and skills of the hospital development team related to marketing strategies through the Hospital Corporate Social Responsibility (CSR) approach. The solutions offered include education on CSR concepts and methods in hospital marketing, CSR implementation training, and assistance in developing strategies and user interfaces for customer data collection. The output of this activity includes the publication of the results of service in scientific journals, videos of online activities, increasing the knowledge and skills of the hospital development team, and integrating the results of the activities into the Hospital Marketing Management course. This activity is expected to be able to strengthen the ability of Hidayah Boyolali Hospital to compete and increase patient satisfaction and loyalty.